1981
DOI: 10.1111/j.1365-2125.1981.tb01321.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the transplacental gradients of bupivacaine and alpha 1‐acid glycoprotein.

Abstract: 1 The binding of bupivacaine (400 ng/ml) to isolated al-acid glycoprotein was studied at two protein concentrations. At 20 mg/10O ml the extent of bupivacaine binding was 31.0 ± 1.8% (mean + s.d., n = 4), and at a protein concentration of 60 mg/100 ml binding of bupivacaine was 85.8 + 1.5% (n = 4).2 Bupivacaine and a,-acid glycoprotein concentrations were measured in plasma samples collected from a maternal peripheral vein and the umbilical vein at delivery (n = 23). The ratio of the foetal:maternal bupivacain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This is due in part to the maternal state of hypoalbuminaemia, but the fetal concentration is still less than that in the average non-pregnant adult. In contrast, term fetal aI-acid glycoprotein plasma concentrations are only 30 to 40% of maternal concentrations (Petersen et al 1981;Wood & Wood 1981). During the first week of life neonatal aI-acid glycoprotein levels double, thus approaching adult concentrations (Philip & Hewitt 1983).…”
Section: Factors Affecting Maternal and Fetal Plasma Protein Bindingmentioning
confidence: 81%
“…This is due in part to the maternal state of hypoalbuminaemia, but the fetal concentration is still less than that in the average non-pregnant adult. In contrast, term fetal aI-acid glycoprotein plasma concentrations are only 30 to 40% of maternal concentrations (Petersen et al 1981;Wood & Wood 1981). During the first week of life neonatal aI-acid glycoprotein levels double, thus approaching adult concentrations (Philip & Hewitt 1983).…”
Section: Factors Affecting Maternal and Fetal Plasma Protein Bindingmentioning
confidence: 81%
“…There is no evidence from this study to support the theory that low fetal: maternal ratios of bupivacaine are caused by extensive fetal tissue uptake [16]. Low feto: maternal ratios are predominantly the effect of differences in o^-acid glycoprotein concentrations [17].…”
Section: Discussionmentioning
confidence: 58%
“…As gestation progresses, α1-acid glycoprotein plasma concentration decreases [37]. Since only protein-unbound drugs are available to cross the placenta, the lower α1-acid glycoprotein levels in pregnant women at term implicate a higher unbound fraction of bupivacaine and, consequently, in a higher placental transfer [38,39]. In this context, Tsen et al [37] demonstrated that an increase in the free fraction of bupivacaine was observed with increasing gestational age and with decreasing α-1 acid glycoprotein plasma concentration [37].…”
Section: Discussionmentioning
confidence: 99%